Accuration of Circulating Tumor DNA (ctDNA) in Detection of Epidermal Growth Factor Receptor (EGFR) Mutation in Lung Cancer Patient Type Adenocarcinoma in M Djamil Hospital Padang - Yandra Darusman; Sabrina Ermayanti; Sari Nikmawati; Afriani Afriani (Respiratory Science, 2020)
Background: ctDNA is an alternative test for detecting mutation of EGFR in lung cancer type adenocarcinoma if the tissue speciment can not be carried out. Sensitivity, specificity and accuration of ctDNA test is stil varied. This study is aimed to acknowledge sensitivity, specificity and accuration of ctDNA in detecting EGFR mutation in patient with lung cancer type adenocarcinoma in M Djamil Hospital. Methods: Design this study a diagnostik test comparing ctDNA to tissue speciment in detection EGFR mutation of 42 patients with lung cancer type adenocarcinoma in M Djamil Hospital. Sample was selected through consecutive technique. Results: Incidence of EGFR mutation in patients with lung cancer type adenocarcinoma from tissue speciment was higher than ctDNA ((42,9% vs 28,6%; p=0,031). There was significant diffierence of EGFR mutation detection between sex, smoking status, and TNM staging based on tissue/cytology examination and ctDNA (p=0,031). EGFR mutation in sitologic test and ctDNA was more likely detected in male patient (66.7% and 58.3%), ex-smoker (50% and 41.7%) and stage IV (88.9% and 91.7%). The results of sensitivity, specificity positive prediction value (PPV) and Negative prediction value (NPV) in ctDNA test to detect EGFR mutation were 66,7%, 100%, 100% dan 80% according to sitology test as gold standard. Furthermore, the ctDNA accuration was measured according to AUC score 0.833 (SE 0,072, CI 95%, 0,693-0,974, p=0.0001). Conclusion: ctDNA test have a good accuration with sensitiviy 66.7% and specificity 100% in detecting EGFR mutation in patients with lung cancer type adenocarcinoma.